A Library in the Palm of Your Hand? A Randomized Reading Intervention with Low-Income Children - Silke Anger; Bernhard Christoph; Agata Galkiewicz; Shushanik Margaryan; Frauke Peter; Malte Sandner; Thomas Siedler (Institute of Labor Economics (IZA), 2024)
Reading skills are crucial for academic success and long-term educational attainment. However, children from disadvantaged backgrounds read less than their more privileged peers. This study assesses the impact of a randomized reading intervention conducted in Germany targeting 11–12-year-olds from low-income households. The intervention involved distributing e-book readers, which provided free access to a large digital library of age-appropriate books, directly to the children's homes. Our results show that the intervention led to increased reading engagement among the children, which in turn improved their academic performance, particularly in reading comprehension and math. Additionally, we observe positive effects on their socio-emotional well-being.
Keywords: C93; I20; I24; 330; randomized controlled trial; low socioeconomic status; reading comprehension; early education